The Arc of History: Will a Draft Bill Finally Bring Justice for Victims of Coercive Sterilization in the Czech Republic? - Cahn, Claude (Romano džaniben, 2019)
This article summarizes state-of-play in efforts of victims of coercive sterilization to secure effective remedy, and in particular to receive financial compensation, a component of this fundamental right. The victims include in particular Romani women as well as women with disabilities, older women and intersex, although there is only limited documentation as concerns some of these groups. Coercive sterilization took place by policy in late Communist Czechoslovakia, and continued throughout the 1990s and into the 2000s in both Czechoslovak successor states, even though official policies guiding these practices had ended. This article focusses in particular on developments in Czechia, where there has been greater public acknowledgement of the practices than in Slovakia, including as a result of a 2009 official expression of regret on the part of the government. In particular, the article endeavors to provide an explanatory basis for a bill currently before Czech Parliament which would provide financial compensation to victims.